Modelling permafrost hydrology using limited data - Xia, Zhao-Jun (My University, 1993)
The hydrological processes of the active layer in continuous permafrost areas are governed by water and energy fluxes, with most hydrological activities concentrated in the thawed seasons. This study was focused on the modelling of hydrological processes in the active layer, emphasizing the fluctuations of the frost table and the moisture status in the thawed zone. Emphases were placed on the calibration of a one-dimensional hydrological model and the development of a two-dimensional model to simulate frost table descent during the summer time. Woo and Drake (1988) developed a model to simulate the daily hydrological and thermal processes of a vertical column in continuous permafrost areas. It combines freeze-thaw processes with water balance to enable daily updating of the status of the frost table, water table, soil moisture, snowmelt and evaporation. Input data include only precipitation, global solar radiation, and air temperature. This model has not been calibrated for the High Arctic and only limited field testing has been performed. This study used field measurements from Resolute, Northwest Territories, to calibrate the model. Independently by obtained data sets were used to test the model outputs and compared with field measurements. The model performed well. The model was then applied to simulate the hydrological responses to climatic variability. The sensitivity of the model was analyzed and discussed. The frost table represents the dynamic lower boundary of the thawed zone. The horizontal variation in frost table depth was modeled, applying the Green theorem to solve the heat flow equation for the active layer zone where the 0$\sp\circ$C isotherm is the limit of thaw. This model incorporates the effect of ground ice content in the retardation of thawing front descent, and the moisture status in the calculation of thermal conductivity. The frost table computed for a transect comprising two distinct soil segments compared favourably with field measured values. The model was used to assess frost table responses to varying degrees of soil saturation, ice content and air temperatures. This model was also coupled to the outputs from the one-dimensional model to allow horizontal extension of the frost table simulations. Coupling of these two models enable hydrological simulation of continuous permafrost terrain using limited input data that can be obtained from Arctic Weather Stations.
Keywords: Hydrology; Hydrology